2021
DOI: 10.1002/anie.202109258
|View full text |Cite
|
Sign up to set email alerts
|

Smart Tumor‐Cell‐Derived Microparticles Provide On‐Demand Photosensitizer Synthesis and Hypoxia Relief for Photodynamic Therapy

Abstract: Positioning essential elements of photodynamic therapy(PDT) near to mitochondria can conquer the rigorous spatiotemporal limitations of reactive oxygen species (ROS) transfer and make considerable differences in PDT.However, precise accumulation of photosensitizer (PS) and oxygen within mitochondria is still challenging. We simultaneously encapsulated hexyl 5-aminolevulinate hydrochloride (HAL) and 3-bromopyruvic acid (3BP) into microparticles collected from X-ray-irradiated tumor cells (X-MP). After systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“… 279 3‐Bromopyruvate inhibits hexokinase‐II activity, thereby inhibiting mitochondrial respiration and glycolysis and reducing mitochondrial oxygen consumption and ATP production. 280 Yu constructed a vesicular photodynamic therapy (PDT)‐specific PV‐TS nanoeconomizer, and an oxygen‐saver concept was proposed. PV‐TS can respond to tumor reduction conditions by releasing NO to inhibit cellular respiration, thereby reducing oxygen consumption and enabling biochemical redistribution of cellular oxygen resources to conserve oxygen.…”
Section: Ways To Improve Intratumoral Oxygenationmentioning
confidence: 99%
“… 279 3‐Bromopyruvate inhibits hexokinase‐II activity, thereby inhibiting mitochondrial respiration and glycolysis and reducing mitochondrial oxygen consumption and ATP production. 280 Yu constructed a vesicular photodynamic therapy (PDT)‐specific PV‐TS nanoeconomizer, and an oxygen‐saver concept was proposed. PV‐TS can respond to tumor reduction conditions by releasing NO to inhibit cellular respiration, thereby reducing oxygen consumption and enabling biochemical redistribution of cellular oxygen resources to conserve oxygen.…”
Section: Ways To Improve Intratumoral Oxygenationmentioning
confidence: 99%
“…62 In a study on the EV-modified PS, capsuled 5-HAL with tumor-derived EVs showed the property of specifically targeting and recognizing tumor cells. 63 However, it is worth noting that cancerous EVs might contain some oncogenes and lead to unintended consequences. Thus, circumspect research and evaluation are needed before the widespread application.…”
Section: Research On the Precision Of Photodynamic Therapy In Pre-cli...mentioning
confidence: 99%
“…[39][40] Zuo et al used tumor-cell released microvesicles to load drugs and achieved highly effective antitumor effects through the specific tumor-targeting ability of MVs. [41] Moreover, irradiated tumor-cell released MVs (RT-MVs) exhibit unique and broad antitumor abilities, and the yield of RT-MVs is significantly higher than that of unirradiated tumor cell-derived MVs. Wan found that, upon injection of RT-MVs into tumor-bearing mice, substantial amounts of RT-MVs were endocytosed by M2 tumor-associated macrophages (M2-TAMs), which were then polarized to anti-tumoral M1 macrophages.…”
Section: Tumor Cell-derived Evsmentioning
confidence: 99%
“…Zuo et al. used tumor‐cell released microvesicles to load drugs and achieved highly effective antitumor effects through the specific tumor‐targeting ability of MVs [41] . Moreover, irradiated tumor‐cell released MVs (RT‐MVs) exhibit unique and broad antitumor abilities, and the yield of RT‐MVs is significantly higher than that of unirradiated tumor cell‐derived MVs.…”
Section: The Sources Of Evs and Their Application For Tumor Therapymentioning
confidence: 99%